PHRASEOLOGY RELATED TO BODY PARTS: A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK EXPRESSIONS - Kasimova Nafisa Farhadovna,; Gafurjanova Ferangiz, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Phraseological  units,  particularly  idioms  involving  body  parts,  constitute  an integral  part  of  both  linguistic  expression  and  cultural  identity.  They  reflect  how different  societies  conceptualize  the  human  body,  emotions,  and  behavior  through figurative language. This article investigates English and Uzbek idioms with body-part components,  analyzing  their  literal  and  figurative  meanings,  cultural  connotations, translation challenges, and underlying conceptual metaphors. By comparing idioms across the two languages, the study identifies universal metaphorical patterns as well as  culture-specific  features, offering valuable  insights  for  linguists,  translators, and language learners.